High Normal Urinary Albumin–Creatinine Ratio Is Associated With Hypertension, Type 2 Diabetes Mellitus, HTN With T2DM, Dyslipidemia, and Cardiovascular Diseases in the Chinese Population: A Report From the REACTION Study - Wang, Jie; Wang, Yun; Li, Yijun; Hu, Ying; Jin, Lingzi; Wang, Weiqing; Gao, Zhengnan; Tang, Xulei; Yan, Li; Wan, Qin; Luo, Zuojie; Qin, Guijun; et al. (Frontiers in Endocrinology, 2022)
Background: Albuminuria has been widely considered as a risk factor for cardiovascular diseases (CVDs)，which is associated with hypertension (HTN), type 2 diabetes mellitus (T2DM), HTN with T2DM and dyslipidemia. However, the associations between albuminuria and HTN, T2DM, HTN with T2DM, dyslipidemia and CVDs are still unclear. Thus, this study is aimed to explore the association of albuminuria thoroughly, especially within the normal range, with the abovementioned diseases in the Chinese population. Methods: This study included 40188 participants aged over 40 years from seven centers across China. Urinary albumin-creatinine ratio (UACR) was firstly divided into the ≥ 30 mg/g group, indicating kidney damage, and < 30 mg/g group. Furtherly, UACR was divided into five groups: the < 20% group, the 20–39% group, the 40–59% group, the 60–79% group and the ≥ 80% group, according to the quintile division of participants within the normal range. Propensity score matching was used to reduce bias, and multiple logistic regression models were conducted to examine the association between UACR and HTN, T2DM, HTN with T2DM, dyslipidemia and CVDs. Results: Multivariable regression analysis revealed that UACR, even within the normal range, is significantly associated with HTN, T2DM, HTN with T2DM, dyslipidemia and CVDs, and the association between UACR and HTN with T2DM was the most significant in model 3 even after adjusting for confounding factors (HTN: OR: 1.56, 95%CI: 1.45-1.68, P<0.0001; T2DM: OR: 1.78, 95%CI: 1.60-1.97, P<0.0001; HTN with T2DM: OR: 1.76, 95%CI: 1.59-1.95, P<0.0001; Dyslipidemia: OR: 1.08, 95%CI: 1.01-1.14, P=0.0146; CVDs: OR: 1.12, 95%CI: 1.00-1.25, P=0.0475). In the stratified analysis, high normal UACR was significantly associated with HTN, T2DM, HTN with T2DM, dyslipidemia in subgroups. Conclusions: We conclude the higher prevalence of HTN, T2DM, HTN with T2DM, dyslipidemia and CVDs in abnormal UACR and reveal a significant association of UACR, even within the normal range, with HTN, T2DM, HTN with T2DM, dyslipidemia and CVDs.